EFEK EKSTRAK METANOL MAKROALGA COKELAT (SARGASSUM SP.), MERAH (GRACILLARIA SP.) DAN TAURIN TERHADAP GAMBARAN HISTOPATOLOGI HEPAR MENCIT JANTAN (MUS MUSCULUS) YANG DIINDUKSI BENZO(?)PIREN - Hervidea, Radella; Widiastuti, Endang Linirin; Nurcahyani, Endang; Sutyarso, Sutyarso; Susanto, G. Nugroho (Perhimpunan Biologi Indonesia, 2018)
ABSTRACTCancer is a disease marked by the existence of abnormal growth of cell continuously and uncontroll in an organism body. Benzo(?)pyrene is one of the substances that can cause a cancer. The methanolic extract of Sargassum sp. and Gracillaria sp. has anticancer and antioxidant activity. Other compounds with antioxidant activity is taurine. The aim of this research is to examine the effect from methanolic extract of Sargassum sp. and Gracillaria sp .and also taurine on hepar histopatology of male mice (Mus musculus) induced by benzo(a)pyrene. This research used Completely Randomized Design. 30 male mice were divided into 6 groups of treatments, those were: K1 = (K-), K2= induced by benzo(?)pyrene for 10 days, K3= after induced by benzo(?)pyrene, were given the Sargassum sp. orally with a dose 8mg/mice during 15 days, K4=after induced by benzo(a)pyrene, were given the combination of Sargassum sp. (8mg/mice) and taurine(15,6mg/mice) orally during 15 days, K5= after induced by benzo (?)pyrene, were given the Gracillaria sp.orally with a dose 8mg/mice during 15 days, and K6=after induced by benzo(a)pyrene, were given the combination of Gracillaria sp. (8mg/mice) and taurine (15,6mg/mice) orally during 15 days. Data were analyzed using ANOVA (? = 5%). The result shows that the combination of Sargassum sp. and Gracillaria sp. and taurine can increase the number of erythrocyte , decrease the number of leucocyte and protect the damage of hepar histopatology of male mice (Mus musculus) induced by benzo (?)pyrene. Combination of extract Gracillaria sp. and taurine is the most effective to protect the damage hepar histopatology of male mice(Mus musculus) induced by benzo(? )pyrene.Keywords: male mice,Sargassum sp., Gracillaria sp., taurine, benzo(a)pyrene, hepar